2017
DOI: 10.1016/j.mehy.2017.05.013
|View full text |Cite
|
Sign up to set email alerts
|

LDL-C levels in older people: Cholesterol homeostasis and the free radical theory of ageing converge

Abstract: The cardiovascular disease (CVD) risk factor, low density lipoprotein cholesterol (LDL-C) increases with age, up until the midpoint of life in males and females. However, LDL-C can decrease with age in older men and women. Intriguingly, a recent systematic review also revealed an inverse association between LDL-C levels and cardiovascular mortality in older people; low levels of LDL-C were associated with reduced risk of mortality. Such findings are puzzling and require a biological explanation. In this paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 49 publications
(50 reference statements)
0
17
0
Order By: Relevance
“…Consequently, oxidative stress results in IR within adipose and peripheral tissue (133) . It has been suggested that high levels of ROS impinge on intracellular cholesterol homeostasis (134) . ROS have been found to upregulate the activity of hepatic HMGCR in rodent hepatic tissue, leading to an increase in cholesterol synthesis (80; 135; 136; 137) ROS are also implicated in the pathogenesis of atherosclerosis, where oxidation of LDL is regarded as a key event in the initial stages of atherosclerosis formation (138) .…”
Section: Commonality Between Obesity and Ageingmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, oxidative stress results in IR within adipose and peripheral tissue (133) . It has been suggested that high levels of ROS impinge on intracellular cholesterol homeostasis (134) . ROS have been found to upregulate the activity of hepatic HMGCR in rodent hepatic tissue, leading to an increase in cholesterol synthesis (80; 135; 136; 137) ROS are also implicated in the pathogenesis of atherosclerosis, where oxidation of LDL is regarded as a key event in the initial stages of atherosclerosis formation (138) .…”
Section: Commonality Between Obesity and Ageingmentioning
confidence: 99%
“…Consequently, oxidative stress results in IR within adipose and peripheral tissue (131) . It has been suggested that high levels of ROS impinge on intracellular cholesterol homeostasis (132) . ROS have been found to up-regulate the activity of hepatic HMGCR in rodent hepatic tissue, leading to an increase in cholesterol synthesis (80,(133)(134)(135) .…”
Section: Commonality Between Obesity and Ageingmentioning
confidence: 99%
“…Changes in TC, TG and LDL-C levels that occur in the geriatric population have been inversely associated with all-cause mortality. The association might be a result of decreased cellular antioxidant capacity and LDL-C production described in the free-radical theory of aging (FRTA) [2528]. However, the relationship between LDL-C levels and DM in geriatric populations has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is challenging to see how this is plausible mechanistically. An alternative explanation for these findings could reside within the biochemical mechanisms which govern hepatic cholesterol homeostasis, and how these processes are affected by aging [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this work, a previously enunciated hypothesis is outlined and examined [ 35 ]. It is hoped the examination of this idea will help to explain why low levels of LDL-C have been associated with an increased rate of mortality in the oldest old.…”
Section: Introductionmentioning
confidence: 99%